Biomimetic superhydrophobic metal/nonmetal surface manufactured by etching methods: A mini review - Ge-Zhang, Shangjie; Yang, Hong; Ni, Haiming; Mu, Hongbo; Zhang, Mingming (Frontiers in Bioengineering and Biotechnology, 2022)
As an emergingfringe science, bionics integrates the understanding of nature, imitation of nature, and surpassing nature in one aspect, and organically combines the synergistic complementarity of function and structure-function integrated materials is of great scientific interest. By imitating the microstructure of natural biological surface, the bionic superhydrophobic surface prepared by human beings has the properties of self-cleaning, anti-icing, water collection, anti-corrosion and oil-water separation, and the preparation research methods are increasing. The preparation methods of superhydrophobic surface include vapor deposition, etching modification, sol-gel, template, electrostatic spinning and electrostatic spraying, etc., which can be applied to fields such as medical care, military industry, ship industry, textile. The research on superhydrophobic surface has developed rapidly, although the potential problems have been discovered and raised constantly. In this paper, the different preparation methods of bionic superhydrophobic materials were summarized, especially the etching modification methods, we discussed the detailed classification, advantages and disadvantages of these methods, and the future development direction of the field was prospected.